(untitled) (London Journal of Medical and Health Research, 2024)
Osteoarthrosis (OA) is one of the most common joint diseases. It affects a significant portion of the population, among which the military, who suffer mainly from post-traumatic knee osteoarthrosis. Being aware of this relationship fosters early preventive and/or protective behaviours among health personnel and allows them to proceed with timely therapeutic measures.